Diversity of Immunoglobulin Light Chain Genes in Non-Teleost Ray-Finned Fish Uncovers IgL Subdivision into Five Ancient Isotypes - Guselnikov, Sergey V.; Baranov, Konstantin O.; Najakshin, Alexander M.; Mechetina, Ludmila V.; Chikaev, Nikolai A.; Makunin, Alexey I.; Kulemzin, Sergey V.; Andreyushkova, Daria A.; Stöck, Matthias; Wuertz, Sven; Gessner, Jörn; Warren, Wesley C.; et al. (Frontiers in Immunology, 2018)
The aim of this study was to fill important gaps in the evolutionary history of immunoglobulins by examining the structure and diversity of IgL genes in non-teleost ray-finned fish. First, based on the bioinformatic analysis of recent transcriptomic and genomic resources, we experimentally characterized the IgL genes in the chondrostean fish, Acipenser ruthenus (sterlet). We show that this species has three loci encoding IgL kappa-like chains with a translocon-type gene organization and a single VJC cluster, encoding homogeneous lambda-like light chain. In addition, sterlet possesses sigma-like VL and J-CL genes, which are transcribed separately and both encode protein products with cleavable leader peptides. The Acipenseriformes IgL dataset was extended by the sequences mined in the databases of species belonging to other non-teleost lineages of ray-finned fish: Holostei and Polypteriformes. Inclusion of these new data into phylogenetic analysis showed a clear subdivision of IgL chains into five groups. The isotype described previously as the teleostean IgL lambda turned out to be a kappa and lambda chain paralog that emerged before the radiation of ray-finned fish. We designate this isotype as lambda-2. The phylogeny also showed that sigma-2 IgL chains initially regarded as specific for cartilaginous fish are present in holosteans, polypterids, and even in turtles. We conclude that there were five ancient IgL isotypes, which evolved differentially in various lineages of jawed vertebrates.